Pengaruh Trust Terhadap Kepuasan Jemaat Di Gbkp Wilayah Medan, Dengan Emotional Attachment Sebagai Variabel Moderator - Tarigan, Dewi Setiana (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to examine the effect of trust on congregation satisfaction at GBKP (Gereja Batak Karo Protestan) in the Medan region, with emotional attachment as a moderating variable. This reasearch is a quantitative research approach. The sample was selected using purposive sampling, totaling 318 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that trust has a positive and significant effect on congregation satisfaction. Furthermore, emotional attachment moderates the relationship between trust and congregation satisfaction. These findings highlight the importance of building both trust and emotional bonds between the church and its members to enhance their overall satisfaction in worship and community life within GBKP Medan.